Large-area alloy nanotube arrays with highly-ordered periodicity: Fabrication and characterization. (1st November 2021) - Chu, Jinn P.; Tseng, Kuan-Wei; Liu, Chih-Yu
Graphical abstract: Highlights: Metallic nanotube arrays (MeNTAs) with highly-ordered periodicity are reported. Stainless steel, Cu-, Ni-, Al-, and Ti-based alloys, Cu, Ag, and Au are used for MeNTAs. MeNTAs are made via sputtering over a contact-hole array of photoresist template. MeNTAs reveal many properties typical of nanostructures, including SERS. MeNTAs also show high hydrophobicity. Abstract: For the most part, the fabrication of nanostructures has been limited to some certain materials. In fact, many researchers view alloys as the last piece of the materials puzzle in the field of nanotechnology. This is the first paper to report on the creation of metallic nanotube arrays (MeNTAs) with highly-ordered periodicity using ferrous (stainless steel) and nonferrous (Cu-, Ni-, Al-, and Ti-based) alloys, as well as elemental metals (Cu, Ag, and Au). The proposed 7 mm × 7 mm MeNTAs were fabricated via sputtering over a contact-hole array template created in photoresist. Extensive analysis revealed many properties typical of nanostructures, including enhanced surface-enhanced Raman scattering (SERS) and high hydrophobicity. The proposed nanotubes can be fabricated over a wide range of heights and diameters (from a few hundred nm to 10 µm) in a variety of shapes, including tall cylinders and dishes. MeNTAs could potentially be used as a platform for the development of nanohybrids in conjunction with nanomaterials such as ZnO nanowires.